SERVICE QUALITY ANALYSIS: AN EMPIRICAL STUDY OF CUSTOMER SATISFACTION IN A HEALTHCARE - Humiras Hardi Purba; Fransisca Debora; Choesnul Jaqin; Hendra Adiyatna (Jurnal Teknologi dan Manajemen, 2021)
Business competition is increasingly fierce, demanding that companies must provide the best products and services to customers. The quality of a product or service is an essential aspect for the continuity of a business, especially those attribute items that are directly felt by customers when purchasing or using a product. This study was aimed to analyze the quality of service to customers in a hospital-based on customer preferences. Customer assessment of each hospital quality indicator was performed through filling out questionnaires by inpatients, to determine the gap between the importance and performance levels. The analytical method used was Importance-Performance Analysis-IPA. As many as 25 quality indicators are identified from SERVQUAL. The quality dimension that becomes a priority for improved performance is related to Reliability, Assurance, and Empathy.